Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/mec.15622
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting signatures of introgression in North American box turtle (Terrapene spp.) contact zones

Abstract: Hybridization occurs differentially across the genome in a balancing act between selection and migration. With the unprecedented resolution of contemporary sequencing technologies, selection and migration can now be effectively quantified such that researchers can identify genetic elements involved in introgression. Furthermore, genomic patterns can now be associated with ecologically relevant phenotypes, given availability of annotated reference genomes. We do so in North American box turtles (Terrapene) by d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 138 publications
(190 reference statements)
3
30
0
Order By: Relevance
“…Speciation in the Karnali River Basin could thus be poorly resolved with respect to mitochondrial divergence, with a genetic signal likely obscured by the limited framework within which ancestral alleles could sort, allowing novel haplotypes to arise. More refined molecular approaches, such as reduced-representation genomics [32,33,34,49,50], could potentially provide the necessary resolution, although it will again be compounded by the rampant polyploidy found in Cyprininae.…”
Section: Macrophthalmus S Nepalensis S Raraensis) Occupy Separatementioning
confidence: 99%
“…Speciation in the Karnali River Basin could thus be poorly resolved with respect to mitochondrial divergence, with a genetic signal likely obscured by the limited framework within which ancestral alleles could sort, allowing novel haplotypes to arise. More refined molecular approaches, such as reduced-representation genomics [32,33,34,49,50], could potentially provide the necessary resolution, although it will again be compounded by the rampant polyploidy found in Cyprininae.…”
Section: Macrophthalmus S Nepalensis S Raraensis) Occupy Separatementioning
confidence: 99%
“…Analyzing more than 10,000 unlinked reference-mapped loci, they found that while in the midwestern contact area hybrids are present in low numbers and restricted to F1 generations only, the southeastern contact area included many backcrosses and F2 individuals, providing evidence of higher levels of introgression between the taxa. Interestingly, they found a set of specific loci with steep genomic clines between taxa, strongly correlated with temperature variables, but not with any precipitation or wind-related variables (Martin et al, 2020). The authors interpreted this as evidence of thermal gradients having a strong effect on introgression patterns and predicted that future changes in temperature could significantly affect the integrity of species boundaries within this genus of turtles (Martin et al, 2020).…”
Section: Hybrid Zonesmentioning
confidence: 99%
“…Particularly susceptible to temperature changes are ectotherms, such as North American box turtles (Terrapene sp.). Martin et al (2020) assembled a dataset of samples from more than 350 individuals across two well-studied zones of hybridization within this genus: one in South Eastern United States, between the woodland (T. carolina carolina), Gulf coast (T. c. major), three-toed (T. carolina triunguis) and Florida (T. bauri) box turtles, and the other one in Midwestern United States, between one subspecies of the ornate box turtle, T. ornata ornata, and T. c. carolina (see Martin et al, 2020 and references therein). Based on these replicated instances of contact at the intra and interspecific levels, the authors were also able to study the contrasting effects of selection and migration on hybridization.…”
Section: Hybrid Zonesmentioning
confidence: 99%
“…We also provide several additional functions (see Figure 1) that have considerable use cases, although some seemingly deviate from the ‘core’ bgc workflow. The first of several can be used to map parameter values of bgc clines onto a chromosomal ideogram via the function plot_outlier_ideogram (e.g., Figure 3), Here, bgc results are depicted for a case study examining hybridization between Woodland ( Terrapene carolina carolina ) and Three-toed box turtles ( Terrapene mexicana triunguis ) (Martin et al, 2020). However, some external user-steps are required to use the function.…”
Section: Descriptionmentioning
confidence: 99%
“…Patterns of multi-locus differentiation, as distributed across admixture gradients, have long provided a window into divergence and speciation (e.g., Barton, 1983; Gompert, Mandeville, & Buerkle, 2017). Accordingly, they have been used to map loci associated with adaptation or reproductive isolation (Buerkle & Lexer, 2008; Martin et al, 2020), and as indicators of biotic responses to environmental change (Chafin, Douglas, Martin, & Douglas, 2019). Rather than relating these to patterns in the landscape, contemporary approaches have instead drawn conclusions based on genome-wide ancestries (Gompert & Buerkle, 2009; Fitzpatrick, 2013).…”
Section: Introductionmentioning
confidence: 99%